Extra X, extra questions: Trisomy X syndrome and IgA deficiency – a case report - Leone, Fabrizio; Gori, Alessandra; Cinicola, Bianca Laura; Brindisi, Giulia; Maglione, Vittorio; Anania, Caterina; Zicari, Anna Maria (Frontiers in Immunology, 2024)
While Trisomy X syndrome is typically characterized by developmental and cognitive variations, it is not commonly associated with immunodeficiencies. We report the unique case of a 6-year-old girl with Trisomy X presenting with selective IgA deficiency, challenging the conventional understanding of this chromosomal condition. The patient exhibited recurrent respiratory infections and gastrointestinal symptoms, evaluated in the context of her genetic background of Trisomy X and significantly low levels of IgA (0.03 g/L), yet normal IgG and IgM levels. Immunological assessment revealed a poor response to vaccination to HBV, necessitating an adapted vaccination strategy. Gastrointestinal investigations indicated paradoxical diarrhea secondary to chronic constipation, managed with dietary interventions. The presence of an extra X chromosome raises questions about the potential over-expression of genes that escape X-chromosome inactivation, such as FOXP3, which is crucial for the regulation of regulatory T cells. An abnormal expression of FOXP3 could lead to either heightened immune regulation, increasing susceptibility to infections, or to immune dysregulation. Although Trisomy X is not typically associated with immunodeficiencies, this case, paralleled by another patient with Trisomy X and CVID, suggests a need for further speculative research into possible genetic links. Moreover, a 1969 study reported lower IgA levels in women with an extra X chromosome. In conclusion, this case aims to underscore the necessity for a deeper genetic and immunological evaluation in chromosomal anomalies like Trisomy X to fully understand their speculative impact on immune function.